(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Anatase TiO2 is widely used for pollutant degradation due to its photocatalytic property. Exposure of the surface to UV radiation (sunlight or artificial) generates an electron-hole pair that is responsible for the formation of free radicals such as O2•−in the presence of atmospheric oxygen and HO• in the presence of water. Biomorphic TiO2 plates were produced by infiltration of paper with titanium isopropoxide (TTiP) solution followed by hydrolysis in NH4OH and calcination at temperatures up to 600-1000 ºC, as a new way of fixing TiO2 with the aim of delaying the phase transition from anatase (photoactive) to rutile (inactive). In order to study the effect of addition of zirconia as a dopant on the microstructure and the phase transition from anatase to rutile, the same procedure was used, but with the addition of 5% (m/m) of ZrO(NO3)2 to TTiP. The biomorphic materials were characterized by XRD, specific surface area measurement (using the BET method), EPR, and SEM. Their photocatalytic efficiencies were evaluated in the decoloration of Orange II dye and the inhibition of growth of E. coli bioluminescent bacteria. Using 5% Zr-doped TTiP, with calcination at 800 ºC, bacterial growth was reduced by 23% after 180 minutes, and 70% dye decoloration was achieved in30 hours.